Frost Insulation of Pipe Trenches (Frostisolering av Roergroefter) - Gundersen,Per (1972)
The traditional way of providing heat insulation for water conduits laid in the ground is by placing the insulation concentrically around the conduits. This insulation method is very effective when reduction of heat loss from the conduit to the surroundings is at issue. In order to keep the conduit from freezing when the surroundings are at a temperature below the freezing point, heat may be supplied to a point of constancy. This heat can be supplied by means of electrical thermocables. For water conduits of major size one can make use of the heat magazine inherent in the water's specific heat. This last case postulates a relatively continuous water flow with a water temperature above the freezing point. (Author) Draft trans. of Symposium. Frost i Jord, 23-24 Nov 70, Del 1; Frost i Jord nr. 2, Feb 71, p65-71 (sic).